THE STUDY OF THE WAQF INSTITUTION IN TURKESTAN (The Journal of Interdisciplinary Human Studies, 2026)
After the territories of Turkestan were conquered by the Russian Empire,new changes were introduced into the socio-economic and political systems of the region.Among other things, this led to the abolition of the waqf institution. The waqf institution,property rights, and waqf documents were thoroughly studied by Russian ImperialOrientalists and Soviet colonial authorities. This article discusses the researchers whostudied the waqf institution during those periods and their scholarly works.
Keywords: Russian Empire; Turkestan, waqf institution; property rights; waqf documents